Corynespora cassiicola and Stemphylium lycopersici infection and disease development on tomatoes in Argentina - Franco, Mario Emilio Ernesto (2017)
Two pathogens were isolated from tomatoes with severe chlorosis and necrosis in northwestern Argentina. Monosporic cultures were morphologically characterised and molecularly identified as Stemphylium lycopersici and Corynespora cassiicola. This is the first report of C. cassiicola infecting tomato in Argentina.